Ethical Leadership Strategies of School Principals: Fostering a Harmonious and Productive Teacher Work Environment - Yunita Sari; Slamet Lestari (AL-ISHLAH: Jurnal Pendidikan, 2025)
A harmonious work environment is essential in educational institutions, and ethical leadership plays a crucial role in fostering such an atmosphere. This study analyzes the ethical leadership strategies employed by a principal to promote a positive work environment in an Islamic school in East Lombok. This qualitative study used a case study approach. Data were collected through interviews with the principal and teachers, as well as documentation analysis. The data were analyzed using descriptive qualitative methods to identify key ethical leadership strategies. The findings reveal three primary ethical leadership strategies implemented by the principal: (1) serving as a role model through ethical behavior, (2) effectively managing ethical conflicts within the school, and (3) fostering the development of positive character among staff and students. These strategies contributed to creating a supportive and ethical work environment. The study highlights the importance of ethical leadership in educational settings, emphasizing the principal's role in maintaining professional integrity and encouraging moral behavior. However, the study is limited in scope, as it does not explore other potential factors influencing a positive work environment. Ethical leadership is essential in shaping a positive school culture. Future research should expand to public schools and broader geographical areas to gain a more comprehensive understanding of ethical leadership practices in different educational contexts.